Paragangliomas da Cabeça e Pescoço: A Experiência de um Centro Oncológico do Sul da Europa - Castelhano, Luís (2022)
Introduction: Paragangliomas are usually benign slow-growing tumors, but they are locally invasive and can cause significant morbidity. The aim of this study was to characterize the presenting symptoms, secretory status, genetics, imaging features, treatment modalities, post-treatment complications and survival of patients with head and neck paragangliomas treated at a single institution.Material and Methods: We retrospectively reviewed the clinical records of patients managed at our center between 1997 and 2020.Results: Seventy-three patients were included in the study, encompassing 89 head and neck paragangliomas. Forty-eight patients (65.8%) were female and 15 (20.5%) had multiple tumor sites (including 10 patients with multicentric benign paragangliomas and five with disseminated malignant disease). Regarding location, our series encompassed 40 temporal bone paragangliomas (44.9%), 24 carotid body paragangliomas (27%), 22 vagal paragangliomas (24.7%), two laryngeal paragangliomas (2.2%) and one sinonasal paraganglioma (1.1%). Excessive catecholamine secretion was detected in 11 patients (15.1%). Sixty-four patients (87.7%) underwent genetic testing. Of those, 24 (37.5%) exhibited pathogenic succinate dehydrogenase complex germline mutations. Regarding patients who presented with untreated disease, 45 patients (66.2%), encompassing 55 tumors, underwent surgery as primary treatment modality, 20 (29.4%; 23 tumors) were initially treated with radiotherapy and three patients (4.4%, encompassing three solitary tumors) were kept solely under watchful waiting. Five-year overall survival was 94.9% and disease-free survival was 31.9%.Conclusion: Head and neck paragangliomas are rare, slow-growing but locally aggressive tumors resulting in high morbidity but low mortality rates.